The Relevance of Agrarian Reform to the Sustainable Development Goals: Analysis of Community Land Empowerment for Food Sufficiency and Gender Equality through the Fishbone Diagram Method - Sopyan, Amalia Arofah Puji; Pujiriyani, Dwi Wulan; Christine, Rosye Villanova (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2024)
Abstract: This study aims to examine the state of food sufficiency and gender equality in Purwabakti Village and the relevance of community land empowerment programs in achieving food sufficiency and gender equality. The research follows a qualitative case study approach, collecting data through interviews, observations, and document analysis. Data were analyzed qualitatively using the fishbone diagram method, focusing on four primary variables: human resources, machinery, methods, and materials. Data on malnutrition and stunting indicate that issues of food vulnerability compromise food sufficiency in Purwabakti Village. Furthermore, gender equality remains a challenge within this predominantly patriarchal society. Women tend to fulfill traditional gender roles with domestic responsibilities, while men assume public roles. This patriarchal rural society generally accepts the predominant land ownership by men (as heads of households), reflecting gender inequality. The fishbone diagram analysis indicates that, despite some progress, community land empowerment programs still exhibit limitations in addressing the SDGs, particularly the goals of “zero hunger” and gender equality. Keywords: Access regulation, Rural Communities, Gender inequality, Patriarchal Culture, Woman Empowerment